Understanding the complexity of Tityus serrulatus venom: A focus on high molecular weight components - de Oliveira, Isadora Sousa; Alano-Da-Silva, Nicoly Malachize; Ferreira, Isabela Gobbo; Cerni, Felipe Augusto; de Almeida Gonçalves Sachett, Jacqueline; Monteiro, Wuelton Marcelo; Pucca, Manuela Berto [UNESP]; Arantes, Eliane Candiani (FapUNIFESP (SciELO), 2024)
Tityus serrulatus scorpion is responsible for a significant number of envenomings in Brazil, ranging from mild to severe, and in some cases, leading to fatalities. While supportive care is the primary treatment modality, moderate and severe cases require antivenom administration despite potential limitations and adverse effects. The remarkable proliferation of T. serrulatus scorpions, attributed to their biology and asexual reproduction, contributes to a high incidence of envenomation. T. serrulatus scorpion venom predominantly consists of short proteins acting as neurotoxins (α and β), that primarily target ion channels. Nevertheless, high molecular weight compounds, including metalloproteases, serine proteases, phospholipases, and hyaluronidases, are also present in the venom. These compounds play a crucial role in envenomation, influencing the severity of symptoms and the spread of venom. This review endeavors to comprehensively understand the T. serrulatus scorpion venom by elucidating the primary high molecular weight compounds and exploring their potential contributions to envenomation. Understanding these compounds’ mechanisms of action can aid in developing more effective treatments and prevention strategies, ultimately mitigating the impact of scorpion envenomation on public health in Brazil.
Keywords: Cysteine-rich secretory proteins; Hyaluronidase; Phospholipase; Proteases; Tityus serrulatus